Analisis Profesionalisme Guru PAI Pasca Pelaksanaan Pengawasan di Sekolah Dasar Negeri Gugus Kecamatan Talang Kelapa Banyuasin - Abdullah Idi; Fitri Oviyanti; Asni Asni (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study was to analyze the professionalism of Islamic education teachers after the implementation of supervision at the Gugus Public Elementary School, Talang Kelapa Banyuasin District. A total of 5 teachers and 5 school principals became research respondents using observation, interview and documentation methods. Obtained the results of research on PAI Teacher Professionalism Before Supervision at SDN Negeri Gugus Kec. Talang Kelapa Banyuasin Teacher professionalism in five schools (SDN 35, SDN 2, SDN 10, SDN 23 and SDN 24 Talang Kelapa) was sufficient before being supervised, it's just that the teacher's responsibility still needs supervision related to teacher competence and discipline. Implementation of Supervision of Islamic Education Teachers at SDN Negeri Gugus Kec. Talang Kelapa Banyuasin has been going on as it should. Supervisors carry out their duties in accordance with their responsibilities to direct teachers according to their competence as educators. Supervisors carry out supervisory activities based on provisions which include supervising administrative tools, learning and evaluation processes to coaching teachers. Post-Supervision Implementation of PAI Teacher Professionalism in Public Elementary Schools in the Talang Kelapa Banyuasin District Elementary School there are developments in terms of administration of learning tools, classroom management and evaluation. Teachers are enthusiastic about developing themselves from the results of supervisor guidance, the teacher's sense of responsibility in developing their competence is getting bigger with the supervisor's direction during supervision.